EFFICACY OF PICHHA BASTI IN ULCERATIVE COLITIS: AN OBSERVATIONAL STUDY - Chiterlekha,; S. Deshpande, Swati; Mishra, Baidyanath (International Journal of Ayurveda and Pharma Research, 2015)
Ulcerative colitis is a chronic idiopathic inflammatory bowel disease with a relapsing nature. It is a very challenging disease affecting a patient during the most active period of his life i.e. 20 to 40 years of age. The main features are ano-rectal bleeding with increased frequency of bowel evacuation, general debility and abnormal structural pathology in the descending colon, particularly sigmoid colon. In modern medical science, there is no permanent curative treatment for this disease. This study can be helpful for reducing the need of steroids and surgical processes in the patients of ulcerative colitis. A clinical study of 5 patients of ulcerative colitis has been conducted at the O.P.D. and I.P.D. SKAMC & RH, Bangalore. They were treated with Pichha basti for 8 days in Yoga basti schedule. Results were analyzed statistically by using the t test. In this study, it was observed that the symptoms and signs were reduced by more than 73% with a highly significant result.